Revision of Camarota Meigen (Diptera: Chloropidae), with a new species from Uganda - Riccardi, Paula Raile; Von Tschirnhaus, Michael (Zootaxa, 2018)
The genus Camarota is revised with the description of a new species—C. ugandae—and a key to species. The genus Paracamarota Cherian is considered here as a new junior synonym of Camarota. Distinctive morphological characters, such as the dark transverse band on the arista, the “vena spuria” of the wing and the placement of apical scutellar bristles, are interpreted.